Out-of-Plane Transport of 1T-TaS2/Graphene-Based van der Waals Heterostructures - Boix-Constant, Carla; Mañas-Valero, Samuel; Córdoba, Rosa; Baldoví, José J; Rubio, Ángel; Coronado, Eugenio (ACS nano, 2021)
Due to their anisotropy, layered materials are excellent candidates for studying the interplay between the in-plane and out-of-plane entanglement in strongly correlated systems. A relevant example is provided by 1T-TaS2, which exhibits a multifaceted electronic and magnetic scenario due to the existence of several charge density wave (CDW) configurations. It includes quantum hidden phases, superconductivity and exotic quantum spin liquid (QSL) states, which are highly dependent on the out-of-plane stacking of the CDW. In this system, the interlayer stacking of the CDW is crucial for interpreting the underlying electronic and magnetic phase diagram. Here, atomically thin-layers of 1T-TaS2 are integrated in vertical van der Waals heterostructures based on few-layers graphene contacts and their electrical transport properties are measured. Different activation energies in the conductance and a gap at the Fermi level are clearly observed. Our experimental findings are supported by fully self-consistent DFT+U calculations, which evidence the presence of an energy gap in the few-layer limit, not necessarily coming from the formation of out-of-plane spin-paired bilayers at low temperatures, as previously proposed for the bulk. These results highlight dimensionality as a key effect for understanding quantum materials as 1T-TaS2, enabling the possible experimental realization of low-dimensional QSLs.